Bimbingan Karir Bagi Kelas XII (Studi Analisis Terhadap Program PSG (Pemulung Sampah Gaul) dan Perpustakaan Masuk Kelas di SMA III Annuqayah Guluk-guluk Sumenep Madura): (Pemulung Sampah Gaul) dan Perpustakaan Masuk Kelas di SMA III Annuqayah Guluk-guluk Sumenep Madura) - Maida Maida (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2021)
AbstractThis research was conducted based on the importance of career guidance for Grade XII. Some ofthe main ideas are students of grade XII are always confused about taking steps after graduatingfrom high school. Some of them have no idea at all to take the next step after graduating from highschool. Another problem when they are going to continue to the college is an incompatible betweentheir interest and the their parents’ hope. While, to start a business, they do not have muchexperience of work, either to be employee or to start their own business. The guidance counselingunit at SMA III Annuqayah Guluk-guluk Sumenep Madura is an urgent unit that cares to thoseproblems and provides a unique and targeted career to the students. The main factor of researcherinterested in doing this research is seeing many facts, especially in Madura which does not careabout the circumstances and problems faced by end grade students. Thus, the researcher wants toexpose how important the career guidance for grade XII. The school should give attention and solvethe problems, so the students have the opportunity to think well in making decision related to theirfuture careers. This research is qualitative and took the guidance counseling unit at SMA IIIAnnuqayah as the background. The research sample used purposive sampling and snowballsampling. The data collection methods were interviews, observation and documentation. The dataanalysis was conducted with descriptive data analysis developed by Milles and Hubbermanincluded three activities simultaneously, data reduction, data presentation and conclusion. Theresults of this study are, 1) The implementation of the PSG (Gaul scavengers) program is given tograde XII devided into three working group teams, namely; plastic waste team, organic fertilizerteam, and local food team. 2) the implementation of the classroom library program is carried out asan effort to open students' mind by provided interesting readings for students from various types ofwriting and various themes to be discussed and created written works. 3) There are three obstaclesin the PSG (Gaul scavengers) program, namely: the limited time that students have, the lack offacilities such as sewing machines and special kitchens for the local food team. 4) the obstacles forthe classroom library program are the instability of students’ spirit, the slowness of newspapersdelivery to school, and the lack of figures from the school in producing written works.Kata kunci: Bimbingan Karir, PSG, dan Perpustakaan Masuk Kelas.